Design idea on planning skill training system of real estate development projects in colleges and universities - Li Kecheng; Li Yuhang; Gou Jian (SHS Web of Conferences, 2016)
The planning skill training of the real estate development project in colleges and universities is an important means for the students majored with the real estate operation and valuation to master it. According to the in-depth researches of the real estate developers and many years’ teaching experience, we put forward the design idea of the skill training system. This idea contains three steps: design of training content, design of training mode and design of training system. This idea is helpful for building a sound training system, and is also helpful for the students to effectively carry out skill training, successfully achieve the goal of mastering the vocational skills, and increase the competitiveness of employment after graduation, thus playing a very good reference role in the development of other vocational skill training systems in colleges and universities